O gênero textual tirinha como ferramenta didática para o ensino de língua portuguesa nos anos finais do ensino fundamental - Paz, Denise Araújo Ferreira (2017)
This study aims to investigate the process of meaning construction as a contribution to the development of reading and the reading ability of students of basic education, using the genre tirinha. By the objective traced, it was characterized as an action research of qualitative-interpretative nature. At first, the work approaches the conception of textual genre, in the perspective of Bakhtin (2000), Marcuschi (2004), Junior (2011), Pereira (2011) and Schneuwly and Dolz (2004). It approaches the genre Comic, from the conceptions of Vergueiro (2014), Ramos (2015), Vilela (2015) and Brazil (1998). It establishes a theoretical-conceptual basis about reading as a construction of meanings in HQ, based on the assumptions of Kleiman (2000), Marcuschi (2008) and Orlandi (2007). It also addresses the genre under study and the educational possibilities, based on Vargas and Magalhães (2011) and Vergueiro (2014). The trajectory that we drew started from the analysis of some strips, which make up the intervention activities, object of this study, carried out with 20 students from the 6th grade of Primary School of a public school in the municipality of Salgado de São Félix, PB, resuming reflections based on the theories of Ramos (2014), Vergueiro (2015), Marcuschi (2008), Ramos (2015), Oliveira (2008) and Cristóvão (2008). The collection took place during the accomplishment of a sequence of activities, in which several constitutive aspects of the multimodal genre, comic strips, with a view to the construction of senses were discussed. The analyzes point to the relevance of this genre in reading practices in the classroom, instilling the development of students' reading skills. This statement is justified by the fact that, when working the genre tirinha, we have a didactic resource rich in aspects of signification, with its respective elements that compose it, such as the relationship of verbal and nonverbal, between others, which point to an effective process of teaching reading.